2014
DOI: 10.1536/ihj.13-383
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Vaccines for Hypertension and Dyslipidemia

Abstract: SummaryVaccines are commonly used as a preventive medicine for infectious diseases worldwide, however, clinical trials on an amyloid beta vaccine for Alzheimer's disease represents a new concept in the fi eld of vaccinations. Several recent studies indicate the potential of therapeutic vaccines as well as classical vaccines as preventive medicines. A number of therapeutic vaccines for cancer have been developed as novel immunotherapies. Their targets are usually specifi c antigens in cancer cells, allowing act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…Active vaccination approach could circumvent these drawbacks. Display of self-antigens in a highly dense, repetitive format on the surface of virus-like particles (VLPs) is one approach for inducing strong antibody responses against self-antigens 7 , 8 . VLP display has been successfully used to target self molecules that are involved in the pathogenesis of a variety of chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Active vaccination approach could circumvent these drawbacks. Display of self-antigens in a highly dense, repetitive format on the surface of virus-like particles (VLPs) is one approach for inducing strong antibody responses against self-antigens 7 , 8 . VLP display has been successfully used to target self molecules that are involved in the pathogenesis of a variety of chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore synthesized the HlgA123-133 peptide as a conjugate with the keyhole limpet hemocyanin (KLH) carrier protein, which is known to be highly immunogenic and provides many T-cell epitopes. Indeed, KLH has been used extensively in prospective candidate vaccines evaluated in murine experiments and in human clinical trials (42). Using this conjugate, mice were primed, then boosted, and the resultant postimmunization sera were tested for binding against a panel of S. aureus toxins and peptides that included the immunizing peptide.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, antibodies against Ang II are not usually produced. For this reason, Ang II peptide was conjugated with the KLH of a carrier protein with both B-cell and T-cell epitopes2223. A previous study revealed that this conjugate, defined as the Ang II vaccine, induced the production of anti-Ang II antibodies, and led to a therapeutic effect in animal models of hypertension5.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the patient must take medicine every day. Additionally, the long-term treatment of the disease is costly223. These problems may lead to non-compliance3.…”
Section: Discussionmentioning
confidence: 99%